2018
DOI: 10.1111/apa.14240
|View full text |Cite
|
Sign up to set email alerts
|

High‐fibre enteral feeding results in improved anthropometrics and favourable gastrointestinal tolerance in malnourished children with growth failure

Abstract: AimThe practical value of using fibre‐enriched enteral feeding regimens to rehabilitate malnourished children remains inconclusive. This study determined the usage patterns, gastrointestinal tolerance, anthropometrics and safety of high‐fibre enteral feeding in malnourished children with growth failure.MethodsThis Turkish observational study between February 2013 and June 2015 comprised 345 paediatric patients from 17 centres with malnutrition‐related growth failure, with a weight and height of <2 SD percentil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 21 publications
0
10
0
1
Order By: Relevance
“…It must be taken into consideration that most patients with CP had severe motor impairment and the age of GT placement was higher. Other series grouping patients with different diagnosis equally observed an overall improvement [16,27,28], although most studies sampled children suffering from a particular disease, such as CP [1,30], neuromuscular diseases [29], cystic fibrosis [7], chronic kidney diseases [31], and oncological diseases [32]. Concerning the study design, differently from the study conducted by Dispaquale et al in 2018 in impaired children, we excluded patients with genetic disorders as their growth is determined mainly by factors other than nutritional [25].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…It must be taken into consideration that most patients with CP had severe motor impairment and the age of GT placement was higher. Other series grouping patients with different diagnosis equally observed an overall improvement [16,27,28], although most studies sampled children suffering from a particular disease, such as CP [1,30], neuromuscular diseases [29], cystic fibrosis [7], chronic kidney diseases [31], and oncological diseases [32]. Concerning the study design, differently from the study conducted by Dispaquale et al in 2018 in impaired children, we excluded patients with genetic disorders as their growth is determined mainly by factors other than nutritional [25].…”
Section: Discussionmentioning
confidence: 95%
“…In addition, Lalanne et al showed in 2014 in a longitudinal study that this gain was maintained for a long term [26]. Regarding the height outcome, there are certain discrepancies, with studies that similarly agreed that height improves parallel to HEN [27,28], while others concluded growth was stationary and followed no significantly positive trend [7,29]. This different outcome is probably related with non-nutritional factors that can stop growth and with the time of treatment initiation.…”
Section: Discussionmentioning
confidence: 99%
“…However, the condition of a child develops and changes during hospitalization. The reliability of the GIF score on the rst day was relatively low, and its role in predicting death during the entire ICU stay is limited [24]. The mean GIF score for the rst three days can be used to dynamically observe and assess changes in gastrointestinal dysfunction during peak disease development, providing better continuity.…”
Section: Discussionmentioning
confidence: 99%
“…Авторы продемонстрировали хорошую переносимость смесей с пищевыми волокнами и их положи тельное влияние на моторику желудочно-кишечного тракта. Так, доля пациентов с нормальными частотой дефекации и характером стула увеличилась с 70,3 до 92,8% к концу исследования (p = 0,004) [25].…”
Section: таблица 5 смеси для нутритивной поддержкиunclassified